(untitled) (Al-Qamar, 2022)
Sīn, Lām and Fā stand for Salaf, which indicates Salafism; it is initially a very eminent Islamic school of thought. Since Islam was spread over the Arabian world and exceeded all geographical boundaries until it reached the non-Arabian countries and islands; it was known as Islam described by Holy Qur’an, interpreted by Allah’s Messenger (peace be upon Him) and stimulated by Holy Messenger’s companions, their followers and the followers of the followers. The term Salafism was basically introduced to the Ummah for them as it was meat: the people of time who in each and every issue be followed without any doubt. Unfortunately, a large number of groups had born from social and political diachronies that later started claiming independently as to be a good example for others to be followed. Surely none of them could precisely prove themselves hundred percent on right way that had been proven by the earliest golden age of Islam. Each one had professed as Salafi to prove oneself for others a good follower of Salaf. This matchless proclamation got all Ummah into sectarianism and racism. In present time Salafism has become a known symbol for a hierarchal group having different perspectives socially, politically and geographically. This paper is a short composition on the subject. It proves what is and what is not to be meant accurately by Salafism and what modern Salafism stands for?